Mapping the EU tomato supply chain from farm to fork for greenhouse gas emission mitigation strategies. (20th October 2020) - Xue, Li; Cao, Zhi; Scherhaufer, Silvia; Östergren, Karin; Cheng, Shengkui; Liu, Gang
Abstract: Tomato and tomato products are the most consumed vegetables worldwide. However, reduction of their relatively high emission intensity can be a key to mitigating greenhouse gas (GHG) emissions of the agrifood sector. Using the European Union (EU) and its 28 member states as example, we mapped the mass flow and analyzed the efficiency of the entire tomato supply chain from farm to fork for the year 2016. We then explored potentials of a full spectrum of GHG emission mitigation strategies ranging from production‐efficiency improvement to process optimization, food‐waste reduction, trade‐pattern change, and diet‐structure change, both individually and in an integrated framework. The results showed that 63% of tomato loss and waste occurred at the processing and consumption stages (over half in Italy and Spain), and 54% of GHG emissions were from production (notably greenhouse based). Although the reduction of tomato products consumption (considered as the substitution by other vegetables) presented the highest potential of emissions reduction, reducing retailing and consumption waste were found to have great effect on GHG emissions reduction as well for all EU member states, especially for United Kingdom and Germany. The combined effects of different mitigation strategies with high levels of change could reduce GHG emissions by 39% compared to the current level.